Acute small subcortical infarctions on diffusion weighted MRI: clinical presentation and aetiology. Issue 11 (14th October 2005) - Seifert, T; Enzinger, C; Storch, M K; Pichler, G; Niederkorn, K; Fazekas, F
Abstract : Objective: To determine the clinical presentation and aetiology of small subcortical infarctions as found on diffusion weighted magnetic resonance imaging (DWI). DWI is both sensitive and specific in the early detection of acute ischaemic brain lesions irrespective of pre-existing vascular damage. Methods: Ninety three patients were identified showing subcortical or brainstem DWI lesions <1.5 cm in diameter within a maximum of 7 days from the onset of stroke symptoms. The patients' clinical status on admission was reviewed according to the Oxfordshire Community Stroke Project (OCSP). The results of procedures searching for cerebrovascular risk factors, large artery disease, and potential sources of cardiac embolism were included to determine stroke aetiology. Magnetic resonance imaging scans were also reviewed for concomitant changes that could support the aetiologic classification. Results: Only 41 (44.1%) patients presented clinically with a lacunar syndrome according to OCSP criteria. The nine (9.7%) patients who showed two or more DWI lesions in different vascular territories were also significantly more likely to have potential sources of cardiac embolism (5/9, 55.6% v 20/84, 23.8%). Hypertension was significantly more prevalent in the group of patients who showed a microangiopathy related imaging pattern, but this pattern did not exclude the presence of large artery disease or a possible cardioembolic source of stroke. Conclusion: Identification of small subcortical infarctions as the cause of stroke appears quite uncertain based on clinical characteristics only. DWI adds significant aetiologic information but does not obviate the search for other potentially causative mechanisms.